A highly sensitive lateral flow immunoassay for the rapid and on-site detection of enrofloxacin in milk - Alhammadi, Munirah; Yoo, Jingon; Sonwal, Sonam; Park, So Young; Umapathi, Reddicherla; Oh, Mi-Hwa; Huh, Yun Suk (Frontiers in Nutrition, 2022)
Enrofloxacin (ENR) is a veterinary antibiotic used to treat bacterial infections in livestock. It chiefly persists in foods and dairy products, which in turn pose severe risks to human health. Hence it is very important to detect the ENR in the foods and dairy products to safeguard human health. Herein, we attempted to develop a single-step detection lateral flow immunochromatographic assay (LFIA) using gold nanoparticles (AuNPs) for the rapid and on-site detection of ENR in milk samples. An anti-enrofloxacin monoclonal antibody (ENR-Ab) was conjugated with AuNPs for the specific detection of ENR in milk samples. For sensitivity improvement, many optimization steps were conducted on LFIA test strips. The visual limit of detection (vLOD) was found to be 20 ng/mL with a cut-off value of 50 ng/mL in the milk samples. The obtained LOD and cut-off value were within the safety limit guidelines of the Ministry of food and drug safety, South Korea. The test strip showed negligible cross-reactivity with ENR analogs, and other components of antibiotics, this indicates the high specificity of the LFIA test strip towards ENR. The designed test strip showed good reliability. The visual test results can be seen within 10 min without the need for special equipment. Therefore, the test strip can be employed as a potential detection strategy for the qualitative on-site detection of enrofloxacin in milk samples.